2021
DOI: 10.1101/2021.01.22.21249945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute and persistent symptoms in non-hospitalized PCR-confirmed COVID-19 patients

Abstract: BackgroundReports of persistent symptoms after hospitalization with COVID-19 have raised concern of a “long COVID” syndrome. This study aimed at characterizing acute and persistent symptoms in non- hospitalized patients with polymerase chain reaction (PCR) confirmed COVID-19.MethodsCohort study of 445 non-hospitalized participants identified via the Danish Civil Registration System with a SARS-CoV-2-positive PCR-test and available biobank samples for genetic analyses. Participants received a digital questionna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 45 publications
8
74
0
4
Order By: Relevance
“…D'Cruz et al and Taboada et al, analyzing prospectively two cohorts of 119 and 91 severe/critical COVID-19 patients, respectively, showed the presence of dyspnoea on exertion (57%), asthaenia (37%), myalgia (37%), and arthralgia (29%) up to 2 months after symptoms onset and a general decrease in quality of life (mobility, usual activities, self-care, pain/discomfort, anxiety/depression) in 67% of patients at up to 6 months of follow-up (77, 100). However, these widespread long-term symptoms were not only present in severe COVID-19 patients, but also in patients who had mild and moderate disease (72,76,80,94,98,146,159). Carvalho-Schneider et al, in a prospective study on 150 mild/moderate COVID-19 patients at 2 months of follow-up, highlighted dyspnea and asthenia, respectively, in 30 and 40% of patients (74,98).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 98%
“…D'Cruz et al and Taboada et al, analyzing prospectively two cohorts of 119 and 91 severe/critical COVID-19 patients, respectively, showed the presence of dyspnoea on exertion (57%), asthaenia (37%), myalgia (37%), and arthralgia (29%) up to 2 months after symptoms onset and a general decrease in quality of life (mobility, usual activities, self-care, pain/discomfort, anxiety/depression) in 67% of patients at up to 6 months of follow-up (77, 100). However, these widespread long-term symptoms were not only present in severe COVID-19 patients, but also in patients who had mild and moderate disease (72,76,80,94,98,146,159). Carvalho-Schneider et al, in a prospective study on 150 mild/moderate COVID-19 patients at 2 months of follow-up, highlighted dyspnea and asthenia, respectively, in 30 and 40% of patients (74,98).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 98%
“…There were no major differences in the prevalence of symptoms at these two time points other than loss of smell/taste being less common at 12 than 4 weeks from onset. Women and people with higher body mass index were more likely to suffer from persistent illness 16 . Another US study (preprint) of mainly non-hospitalised PCR positive cases (n=357) found a prevalence of symptoms of 36% after 30 days from onset and 15% at 90 days 35 .…”
Section: Main Findings and Comparison To Other Datamentioning
confidence: 99%
“…For example, the ONS study based their estimates on a list of 12 symptoms included in the ONS infection survey 15 , with some of the common symptoms of Long Covid such as chest pain, palpitations and cognitive problems missing from that list. Other studies, some with a wider symptom list, estimate the prevalence of persisting symptoms to be higher at around one in three people for up to 18 weeks post infection 4,5,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Full-text articles of these abstracts were obtained, and study criteria were applied. Thirty-one published studies[53-55 78-105] and eight medRxiv preprints[46 75 106-111], met the inclusion criteria for this systematic review (Figure 1). The sample sizes ranged from 18[102] to 1655[79], with mean age across studies ranging from 32.3 (SD = 8.5)[54] to 67.1 (SD =11.6)[87].…”
Section: Resultsmentioning
confidence: 99%